Effect of micro-dams on water flow characteristics in furrow irrigation - Keshavarz, Mohammad Sadegh; Ebrahimian, Hamed; Abbasi, Fariborz; Playán, Enrique (Irrigation science, 2020)
Surface irrigation, particularly furrow irrigation, is the most common method of water application into agricultural lands. Despite all its advantages, furrow irrigation has some demerits, such as a potential large volume of runoff losses. In this research, an approach was proposed to reduce runoff losses and to improve water flow characteristics by creating micro-dams, barriers inside the irrigated furrows. To control water flow and increase infiltration into the soil, experimental micro-dams were created at distances of 10 and 20 m, with a height of 5 cm. Field experiments were conducted at the research farm of the College of Agriculture and Natural Resources, University of Tehran, Karaj, Iran in summer of 2018. Two erosive inflow rates (0.6 and 0.9 L/s) were considered. Furrow length and spacing were 100 and 0.75 m, respectively. Results indicated that micro-dams increased the advance time, leading to increased infiltration. Micro-dams also increased the recession time, due to the increase in overland water volume. Moreover, results showed that in treatments with micro-dams, runoff was reduced by up to 45.3% in comparison to the control treatment. The change in furrow cross-sectional area during the irrigation event was also reduced. Micro-dams showed a great potential to reduce irrigation runoff losses, and should be considered as a management practice aiming at water and soil conservation.